Universidade do ar: em foco a primeira iniciativa de formação de professores secundaristas via rádio no Estado Novo (1941 1944) - Romero, Maria Helena Cicci (2014)
The present dissertation aims to further study the radio as a way of distance education in Brazilian history and contributions from Roquette-Pinto, first to organize this experience and create the first radio station in Brazil, carrying forward this new technology that profoundly changed Brazilian society in the twentieth century. Fabio Prado Pimentel author of The Educational Radio in Brazil examined education by radio in Brazil featuring the main projects undertaken in this area. According to the author, simultaneously the creation and development of the Educational Broadcasting Service / SRE, some particular stood out experiments in educational broadcasting being alternatives to the official system. The first was to be held at Air University, the National Radio of Rio de Janeiro, created in 1941 by the director of the Issuer, Gilberto Andrade, under the supervision of the Division of Secondary Education of the Ministry of Education and Culture (MEC ), directed by Professor Lucia Magalhães. The pedagogical purpose was to provide high school teachers a new methodology for the submission of disciplines. The reading of this work raised the question about what the intent, territorial coverage, ie regions which the program has achieved and how was this educational phenomenon destined for high school teachers and that it was offered in distance mode via radio with the program University of the Air broadcast by Radio Nacional of Rio de Janeiro. The specific objectives are: to bring a brief discussion of the major studies on the problem of the means of mass communication, emerged during the twentieth century; a brief introduction to the ideas of Brazilian modernity to better understand the context in which the radio was inserted as a vehicle of mass communication; analyze the evolution of the insertion of radio in everyday Brazilian society between 1930-1950; provide distance education as an educational modality emphasizing its history and the first steps of teaching radio in Brazil; assess how have the political and economic discussions of the educational field during the Estado Novo influencing the initiative of Air University program broadcast by Radio Nacional Rio de Janeiro; analyze contributions Roquette Pinto for the insertion of educational radio in Brazil. The methodology was based on qualitative and bibliographic research through the analysis of books and articles of digital media, beyond the critical analysis of documentary sources found in the National Archives of Rio de Janeiro.